BEST PRACTICE OF HOSPITAL MANAGEMENT STRATEGY TO THRIVE IN THE NATIONAL HEALTH INSURANCE (JKN) ERA - Wahyu Pudji Nugraheni; Asri Hikmatuz Zahroh; Risky Kusuma Hartono (Indonesian Journal of Health Administration, 2021)
Background: The implementation of the National Health Insurance (JKN) program has created a transformation in the health care system in Indonesia. Many hospitals were stuttering and unable to adapt to the new payment system. Some hospitals complained about INA-CBG rates that were lower than the real rates, so that hospitals suffered losses.Aims: This research aims to take the best practice from one government hospital and one private hospital that is able to thrive in the JKN era.Methods: This study used qualitative research methods through in-depth interviews.Results: The similarity of strategies carried out by the two best practice hospitals to thrive in JKN era are efficiency in business process, investment in human resources, customer relationship management, and stakeholders collaboration.Conclusion: The results of this study can be used as a reference for government and private hospitals in Indonesia to be able to thrive in the JKN era.Keywords: best practice, hospital, National Health Insurance, strategy